Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

A sea-to-soil solution for the green tides threatening shellfish aquaculture: conceptual model and lessons learned from a pilot project - Sarah M. Collier; Emily Buckner; Nicole J. Capizzi; Meg Chadsey; Douglas P. Collins; Jonathan P. Davis; Erick Dowell; Alan Ismach; Brittany G. Johnson; Sergey Rabotyagov; Rob Smith; Katie R. Webb; et al. (Journal of Environmental Management, 2026)

Temporal myopia in building Life Cycle Assessment? Granular versus coarse dynamics in climate change and grid decarbonisation - Marios Kordilas; Dejan Mumovic; Yair Schwartz; Rob Cooke; Smith Mordak; Zaid Chalabi (Building and Environment, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The impact of evolving mix on building’s life cycle environmental impacts under climate change: insights from a London office case study - Marios Kordilas; Dejan Mumovic; Yair Schwartz; Rob Cooke; Smith Mordak (The International Journal of Life Cycle Assessment, 2025)
Purpose The main aim of this study is to identify how evolutions in the electricity mix and climate change affect the LCA results of buildings regarding the multitude of environmental impacts. This is of critical importance now, and one that is likely to receive growing interest in the future. Firstly, because carbon might become a secondary environmental impact to mitigate as economies achieve decarbonisation milestones, and secondly, due to concerns around the trade-offs between the environmental impacts. Methods This study evaluates the lifecycle environmental impacts of a case study office building in London by considering climate change in the UK (using CIBSE weather files) and electricity mix evolution in the UK (using National Grid ESO data), EU (using EU commission data) and China that influence operational and embodied modules of LCA. Electrification of transport is also considered, reflecting the forementioned electricity mixes. A dynamic LCA approach was followed in which the inventory was modified to reflect future electricity mixes. The influence of climate evolution was considered through dynamic thermal simulations according to London’s future climatic projections provided by CIBSE’s weather files that were then translated into lifecycle environmental impacts through the modified inventory. Results and discussion Results of applying a dynamic approach in LCA show that there are several co-benefits of grid decarbonisation when it comes to the building’s environmental impacts. However, ecotoxicity and land occupation might come to light. Climate change led to minor reductions in the operational electricity needs, indicating that no significant savings are to be expected in the case of actively cooled buildings without free ventilative cooling. Evolving electricity mixes do not significantly reduce material embodied impacts for this case study, showing that the reduction of lifecycle impacts cannot rely only on future electricity mix evolutions. The electrification of transport was found to have an adverse effect on the building’s embodied ionising radiation impact, highlighting the importance of sourcing materials locally to avoid long transportation distances. A new type of performance gap is proposed for the building’s lifecycle environmental impacts. This can be defined as ‘the difference between the predicted and the actual environmental impact resulting from the mismatch between the actual case and the life cycle inventory’. Conclusions Future research is needed to investigate how sensitive results are to other assumptions and how improvements in material manufacturing affect the obtained results.

What controlled the occurrence of more than 116,000 human-mapped landslides triggered by Cyclone Gabrielle, New Zealand? - Chris Massey; Kerry Leith; Tom R Robinson; Biljana Lukovic; Sam McColl; Trevor Carey-Smith; Brenda Rosser; Liam Wotherspoon; Hugh Smith; Harley Betts; Rob Buxton; Janine Bidmead (Landslides, 2025)
This paper uses an extract of 116,655 landslide source areas from the >160,000 human-mapped landslides contained in the Version One (V1.0) landslide inventory triggered by Cyclone Gabrielle (11–17 February 2023). It describes the analysis of the human-mapped landslide distribution and the relationships between landslide occurrence, their susceptibility factors, and their hydrological forcing factors. The results show that rain is one of the main controlling factors on landslide probability, but the relationship is complex. Our results show the amount of 24-h rain becomes less important, relative to other landslide susceptibility factors, at high (>220 mm) to very high (>330 mm) 24-h rainfalls, suggesting that such extreme rain amounts may not drive the highest probability of landslide occurrence. Results also suggest that the 24-h rainfalls experienced by some areas during Cyclone Gabrielle were likely to have been sufficiently high enough to “overprint” antecedent soil water conditions. In these overprint areas, soil-water conditions prior to Cyclone Gabrielle rainfall may not have materially influenced the spatial landslide distributions. The results from this study suggest that during a storm, more intense rainfall may not directly translate to increasing probability of landslide occurrence; however, it may diminish the effect of pre-event soil water content.

Suspended sediment properties and visual clarity of the Manawatū River, New Zealand - Rob J. Davies‐Colley; Andrew O. Hughes; Arman Haddadchi; John R. Dymond; Simon S. Vale; Hugh G. Smith (New Zealand Journal of Marine and Freshwater Research, 2025)
Studies of river suspended sediment typically focus on mass loads with little attention devoted to sediment properties such as particle size distribution (PSD) or light attenuation. However, environmental behaviour and ecological effects of suspended sediment vary greatly with particle properties. Visual clarity is a particularly important attribute of waters that is strongly affected by particle properties. We studied the relationship between visual clarity and suspended sediment in the Manawatū River – by combining event auto‐sampling with long‐term state‐of‐environment monitoring. We fractionated stormflow samples into sand and ‘mud’ (silt + clay) by wet‐sieving at 63 μm, and the mud fraction was further analysed for organics, PSD and light beam attenuation (which controls visual clarity). Light beam attenuation correlated very closely with high‐frequency field turbidity – providing an absolute optical calibration. The ratio of light beam attenuation to mass concentration (known as ‘optical cross‐section’) averaged about 0.5 m 2 /g – somewhat higher than expected for silt particles in the measured size range, probably due to plate‐shaped clays. The visual clarity regime, estimated from field turbidity, was consistent with monthly direct observations. Our study illustrates how certain sediment ‘quality’ metrics can usefully extend sediment monitoring applications, and we encourage closer integration of sediment and water quality monitoring.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Noise from deep-sea mining in the Clarion-Clipperton Zone, Pacific Ocean will impact a broad range of marine taxa - Rob Williams; Kieran D. Cox; Diva Amon; Erin Ashe; Lucille Chapuis; Christine Erbe; Asha de Vos; Kimberly A. Nielsen; Marena Salerno Collins; Craig Smith; Travis Washburn; Kirsten F. Young; et al. (Marine Pollution Bulletin, 2025)

Extreme events drive rapid and dynamic range fluctuations - Lydia G. Soifer; Julie L. Lockwood; Jonas J. Lembrechts; Laura H. Antão; David H. Klinges; Rebecca A. Senior; Natalie C. Ban; Birgitta Evengard; Belen Fadrique; Sophie Falkeis; Alexa L. Fredston; Rob Guralnick; et al. (Trends in Ecology & Evolution, 2025)

Responses of an Old Deciduous Forest Ecosystem to Elevated CO 2 - Christine H. Foyer; Anna Gardner; Scott A. L. Hayward; Rosa Sanchez‐Lucas; Estrella Luna; James E. McDonald; Manon Rumeau; Kris Hart; Richard J. Norby; Carolina Mayoral; Vincent Gauci; Andy Smith; et al. (Global Change Biology, 2025)
The free‐air CO 2 enrichment (FACE) site at the Birmingham Institute of Forest Research (BIFoR) is situated in a long‐established mature, temperate oak‐dominated forest. Over the past 8 years, these tree species have been exposed to elevated CO 2 (eCO 2 target: 150 ppm above ambient). The observed eCO 2 fertilization effect is significant in the mature oak trees, with sustained increases in photosynthesis and stem dry matter production. The fine root standing crop was greater in the eCO 2 plots, and carbon exudation flux was greatly increased, stimulating soil gross nitrogen (N) mineralization, enhanced microbial activity, and enzyme functions. Nitrification was suppressed, particularly in the rhizosphere, pointing towards ecosystem N conservation strategies. Alongside the positive forest productivity response, however, comes evidence of nascent ecosystem fragility, including susceptibility to powdery mildew and insect herbivory that is unchanged in the mature trees but increased in seedlings. Changes to invertebrate food webs were observed, including flower‐pollinator phenologies and detritivore abundances. Pollen and flower mineral contents were significantly reduced under eCO 2 , and acorns contained significantly less protein but more phytic acid, suggesting a carbon‐rich, nutrient‐poor, future diet for animals and insects in natural forest ecosystems.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Strengths and complementarity of systematic conservation planning and Key Biodiversity Area approaches for spatial planning - Andy Plumptre; Jack Hayes; Daniele Baisero; Rob Rose; S. Holness; Lize von Staden; Robert J. Smith (Conservation Biology, 2025)
Developing biodiversity‐inclusive spatial plans at a national level is the focus of Target 1 of the Kunming–Montreal Global Biodiversity Framework (KMGBF). There are 2 general approaches to identifying areas of value for biodiversity plans: criteria‐based, such as the Key Biodiversity Areas (KBA) process, and systematic conservation planning (SCP) approaches, which apply complementarity to efficiently achieve specific quantitative targets. We examined the benefits of both approaches and considered how the KBA approach can best complement SCP. We reviewed 200 papers articles that applied SCP to real‐world data with the Marxan conservation design software. Our review showed that targets for biodiversity elements are poorly selected in many SCP publications, with more than 75% of the studies applying uniform percentage target amounts to planning elements. Uniform targets favor more widespread species and ecosystems that are likely to be more common and less important for conservation. The strengths and complementarities of KBA and SCP approaches were reviewed and we identified the elements from both approaches that should be considered for spatial planning to achieve Target 1 in the KMGBF. In particular, the global approach of KBAs (i.e., identifying sites of global significance for species or ecosystems) better complements SCP, which often has a national or subnational focus. The KMGBF will fail if conservation of globally significant sites is not targeted and these sites are not incorporated in national spatial planning.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Complexity of consumer acceptance to alternative protein foods in a multiethnic Asian population: A comparison of plant-based meat alternatives, cultured meat, and insect-based products - Airu Chia; Yiyun Shou; Nicole Min Yee Wong; David Cameron-Smith; Xueling Sim; Rob M. Van Dam; Mary F.-F. Chong (Food Quality and Preference, 2024)

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Pathways from research to sustainable development: Insights from ten research projects in sustainability and resilience - Anna Scaini; Joseph Mulligan; Håkan Berg; Albert Brangarí; Vera Bukachi; Sebastian Carenzo; Da Chau Thi; Colin Courtney-Mustaphi; Anneli Ekblom; Hanne Fjelde; Mathias Fridahl; Anders Hansson; et al. (Ambio, 2024)
Drawing on collective experience from ten collaborative research projects focused on the Global South, we identify three major challenges that impede the translation of research on sustainability and resilience into better-informed choices by individuals and policy-makers that in turn can support transformation to a sustainable future. The three challenges comprise: (i) converting knowledge produced during research projects into successful knowledge application; (ii) scaling up knowledge in time when research projects are short-term and potential impacts are long-term; and (iii) scaling up knowledge across space, from local research sites to larger-scale or even global impact. Some potential pathways for funding agencies to overcome these challenges include providing targeted prolonged funding for dissemination and outreach, and facilitating collaboration and coordination across different sites, research teams, and partner organizations. By systematically documenting these challenges, we hope to pave the way for further innovations in the research cycle.

Emerging patterns of genetic diversity in the critically endangered Malayan tiger (Panthera tigris jacksoni) - Kate Allberry; Jeffrine Japning Rovie-Ryan; Nur Alizati Nabila Giarat Ali; Nurul-Ain Elias; Mark Rayan Darmaraj; Christopher Chai Thiam Wong; Lau Ching Fong; Olutolani Smith; Khairul Amirin Bin Mohamed; Mohamad Izereen Bin Amat Mukri; Muhammad Hafiz Bin Mohd Yazid; Matthew J. Struebig; et al. (Biodiversity and Conservation, 2024)
Southeast Asia experiences some of the highest deforestation in the world. Loss of tropical forest typically leads to widespread habitat fragmentation, with detrimental effects on dispersal ability and gene flow—particularly for large carnivores. We conducted mtDNA and microsatellite analysis to assess—for the first time—contemporary patterns of genetic diversity in the Malayan tiger. We collected 295 suspected carnivore samples in Peninsular Malaysia, from which we identified 26 as originating from tiger using 16 polymorphic microsatellite loci, comprising 22 individual tigers. Despite limitations of the study, our findings suggest tiger subpopulations in the north of the peninsula maintain some genetic connectivity and migration between two putative geographic subpopulations in the Main Range and Greater Taman Negara, with negligible population segregation due to dispersal barriers such as road infrastructure. We identified consistently lower levels of genetic diversity in tigers in the Greater Taman Negara region compared to tigers in the Main Range and small but emerging differences in nuclear and mitochondrial genetic diversity. Our mtDNA haplotype and nuclear DNA analyses suggest the levels of genetic diversity in Malayan tigers may be amongst some of the lowest of the surviving tiger subspecies, though the study is limited both in scale and genomic loci. Our findings are consistent with an expected lag between the rapid decline of tigers in Peninsular Malaysia by over 95% in the last 70 years and observed differences in their levels of genetic diversity.

Impacts of Extratropical Cyclone Fiona on a sensitive coastal lagoon ecosystem - Abigail C. Bonnington; Rob C. Jamieson; Kathryn A. Smith; Allie Oliver; Lindsay H. Johnston; Nicole K. LeRoux; Lauren D. Somers; Barret L. Kurylyk (Limnology and Oceanography, 2023)
Oceanic storms can strongly disturb the physical and biogeochemical conditions of transitional coastal waters. Impacts of extreme oceanic storms on coastal ecosystems have received limited attention worldwide, with no studies at higher latitudes (> 45°) where tropical cyclones have usually abated. This study investigates the combined impacts from marine and atmospheric forcing on a coastal lagoon in Prince Edward Island, Canada, during and after Extratropical Cyclone Fiona in September 2022. Physical (water levels and temperature) and biogeochemical (dissolved oxygen [DO], electrical conductivity, pH, nitrate–nitrogen concentrations, total suspended solids [TSS]) datasets from the lagoon and the watershed's tributaries, groundwater springs, and piezometers were used to assess ecosystem disturbance and recovery timelines following the storm. Fiona resulted in a 1.6 m storm surge into the lagoon that elevated water temperatures by up to 6°C, disturbed the density‐dependent stratification of salinity and temperature, and reduced the diel amplitude of DO, indicating a reduction in plant respiration due to ecosystem disturbance. The freshwater tributaries revealed sharp changes in flow (30‐fold increase), nitrate–nitrogen (NO 3 ‐N) concentrations and loading (70‐fold increase), and TSS loading (40‐fold increase) to the lagoon during and immediately following the storm. The lagoon rapidly recovered (hours) from the hydraulic disturbance of the storm surge, but elevated nutrient levels persisted for months. The intensity and frequency of extratropical cyclones is projected to increase in the Northwest Atlantic, making field‐based studies of cyclone impacts on coastal waters critical for understanding future coastal ecosystem disturbance and recovery periods relative to the timing of future storms.

Modelling wine grapevines for autonomous robotic cane pruning - Henry Williams; David Smith; Jalil Shahabi; Trevor Gee; Mahla Nejati; Ben McGuinness; Kale Black; Jonathan Tobias; Rahul Jangali; Hin Lim; Mike Duke; Oliver Bachelor; et al. (Biosystems Engineering, 2023)

The aetiology and incidence of infective endocarditis in people living with rheumatic heart disease in tropical Australia - Andrew Basaglia; Katherine Kang; Rob Wilcox; Alistair Lau; Kylie McKenna; Simon Smith; Ken W. T. Chau; Josh Hanson (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Purpose To define the incidence and microbiological aetiology of infective endocarditis (IE) in patients with rheumatic heart disease (RHD) in tropical Australia. Methods A retrospective study that examined all episodes of IE between January 1998 and June 2021 among individuals on the RHD register in Far North Queensland, Australia. Results There were 1135 individuals with a diagnosis of RHD on the register during the study period, representing 10962 patient-years at risk. Overall, there were 18 episodes of definite IE occurring in 16 individuals, although only 7 episodes occurred in native valves (11 occurred in prosthetic valves) equating to 0.7 episodes of native valve IE/1000 patient-years. No patient with mild RHD - and only one child with RHD - developed IE during the study period. Despite the study’s tropical location, the causative organism was usually typical skin or oral flora. Among individuals with an indication for benzathine penicillin G (BPG) prophylaxis, only 1/6 episodes of IE due to a penicillin-susceptible organism received BPG in the month before presentation. Conclusion Although RHD predisposes individuals to IE, the absolute risk of IE in native valve disease in tropical Australia is low and might be reduced further by improved adherence to secondary BPG prophylaxis.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Effects of concurrent exercise training on body composition, systemic inflammation, and components of metabolic syndrome in inactive academics: a randomised controlled trial - Samuel M. Higham; Amy E. Mendham; Simon Rosenbaum; Nicholas G. Allen; Greg Smith; Antony Stadnyk; Rob Duffield (European Journal of Applied Physiology, 2023)

Right connection, right insight engaging private estate managers on woodland expansion issues in times of uncertainty - Euan. A.D. Bowditch; Rob McMorran; Melanie. A. Smith (Land Use Policy, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Dedication to Ron Pace - G. Charles Dismukes; Rob Stranger; Paul Smith (Photosynthesis Research, 2022)

Bacterial Viruses Subcommittee and Archaeal Viruses Subcommittee of the ICTV: update of taxonomy changes in 2021 - Mart Krupovic; Dann Turner; Vera Morozova; Mike Dyall-Smith; Hanna M. Oksanen; Rob Edwards; Bas E. Dutilh; Susan M. Lehman; Alejandro Reyes; Diana P. Baquero; Matthew B. Sullivan; Jumpei Uchiyama; et al. (Archives of Virology, 2021)
In this article, we – the Bacterial Viruses Subcommittee and the Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) – summarise the results of our activities for the period March 2020 – March 2021. We report the division of the former Bacterial and Archaeal Viruses Subcommittee in two separate Subcommittees, welcome new members, a new Subcommittee Chair and Vice Chair, and give an overview of the new taxa that were proposed in 2020, approved by the Executive Committee and ratified by vote in 2021. In particular, a new realm, three orders, 15 families, 31 subfamilies, 734 genera and 1845 species were newly created or redefined (moved/promoted).

Prioritizing debt conversion opportunities for marine conservation - Jennifer McGowan; Rob Weary; Leah Carriere; Edward T. Game; Joanna L. Smith; Melissa Garvey; Hugh P. Possingham (Conservation Biology, 2020)
Incentivized debt conversion is a financing mechanism that can assist countries with a heavy debt burden to bolster their long‐term domestic investment in nature conservation. The Nature Conservancy, an international conservation‐based nongovernmental organization, is adapting debt conversions to support marine conservation efforts by small island developing states and coastal countries. Prioritizing debt conversion opportunities according to their potential return on investment can increase the impact and effectiveness of this finance mechanism. We developed guidance on how to do so with a decision‐support approach that relies on a novel threat‐based adaptation of cost‐effectiveness analysis. We constructed scenarios by varying parameters of the approach, including enabling conditions, expected benefits, and threat classifications. Incorporating both abatable and unabatable threats affected priorities across planning scenarios. Similarly, differences in scenario construction resulted in unique solution sets for top priorities. We show how environmental organizations, private entities, and investment banks can adopt structured prioritization frameworks for making decisions about conservation finance investments, such as debt conversions. Our guidance can accommodate a suite of social, ecological, and economic considerations, making the approach broadly applicable to other conservation finance mechanisms or investment strategies that seek to establish a transparent process for return‐on‐investment decision‐making.

Potential carbon loss from Scottish peatlands under climate change - Anna Ferretto; Rob Brooker; Matt Aitkenhead; Robin Matthews; Pete Smith (Regional Environmental Change, 2019)

What can cetacean stranding records tell us? A study of UK and Irish cetacean diversity over the past 100 years - Ellen J. Coombs; Rob Deaville; Richard C. Sabin; Louise Allan; Mick O'Connell; Simon Berrow; Brian Smith; Andrew Brownlow; Mariel Ten Doeschate; Rod Penrose; Ruth Williams; Matthew W. Perkins; et al. (Marine Mammal Science, 2019)
There are many factors that may explain why cetaceans (whales, dolphins, and porpoises) strand. Around the UK and Ireland, over 20,000 stranding records have been collected since 1913, resulting in one of the longest, continuous, systematic stranding data sets in the world. We use this data set to investigate temporal and spatial trends in cetacean strandings and use generalized additive models (GAMs) to investigate correlates of strandings. We find a dramatic increase in strandings since the 1980s, most likely due to increases in recording effort, and the formation of formal strandings networks. We found no correlation between the numbers of cetaceans stranding each year and several potential environmental and anthropogenic predictors: storms, geomagnetic activity, North Atlantic Oscillations, sea‐surface temperature, and fishing catch. We suggest that this is because the scale of change in the variables is too coarse to detect any potential correlations. It may also highlight the idiosyncratic nature of species’ responses to external pressures, and further the need to investigate other potential correlates of strandings, such as bycatch and military sonar. Long‐term cetacean stranding data provide vital information on past and present diversity for common, rare, and inconspicuous species. This study underlines the importance of continued support for stranding networks.

Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales - Christel Prudhomme; Jamie Hannaford; Shaun Harrigan; David Boorman; Jeff Knight; Victoria Bell; Christopher Jackson; Cecilia Svensson; Simon Parry; Nuria Bachiller-Jareno; Helen Davies; Richard Davis; et al. (Hydrological Sciences Journal, 2017)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Tiger (Panthera tigris) scent DNA: a valuable conservation tool for individual identification and population monitoring - Anthony Caragiulo; Rob Stuart Alexander Pickles; Joseph Alexander Smith; Olutolani Smith; John Goodrich; George Amato (Conservation Genetics Resources, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Carbon loads, forms and sequestration potential within ash deposits produced by wildfire: new insights from the 2009 ‘Black Saturday’ fires, Australia - Cristina Santín; Stefan H. Doerr; Richard A. Shakesby; Rob Bryant; Gary J. Sheridan; Patrick N. J. Lane; Hugh G. Smith; Tina L. Bell (European Journal of Forest Research, 2012)

Quantitative multi-risk analysis for natural hazards: a framework for multi-risk modelling - Jochen Schmidt; Iain Matcham; Stefan Reese; Andrew King; Rob Bell; Roddy Henderson; Graeme Smart; Jim Cousins; Warwick Smith; Dave Heron (Natural Hazards, 2011)

Development of a Murine Model with Optimal Routes for Bacterial Infection and Treatment, as Determined with Bioluminescent Imaging in C57BL/6 Mice - Anneke M. Brand; Rob Smith; Michele de Kwaadsteniet; Leon M. T. Dicks (Probiotics and Antimicrobial Proteins, 2011)

What do near-term observations tell us about long-term developments in greenhouse gas emissions? - Detlef P. van Vuuren; Jae Edmonds; Steven J. Smith; Kate V. Calvin; Joseph Karas; Mikiko Kainuma; Nebojsa Nakicenovic; Keywan Riahi; Bas J. van Ruijven; Rob Swart; Allison Thomson (Climatic Change, 2010)

Age assignment of a diatomaceous ooze deposited in the western Amundsen Sea Embayment after the Last Glacial Maximum - Claus‐Dieter Hillenbrand; James A. Smith; Gerhard Kuhn; Oliver Esper; Rainer Gersonde; Rob D. Larter; Barbara Maher; Steven G. Moreton; Tracy M. Shimmield; Monika Korte (Journal of Quaternary Science, 2010)
Reliable dating of glaciomarine sediments deposited on the Antarctic shelf since the Last Glacial Maximum (LGM) is challenging because of the rarity of calcareous (micro‐) fossils and the recycling of fossil organic matter. Consequently, radiocarbon ( 14 C) ages of the acid‐insoluble organic fraction (AIO) of the sediments bear uncertainties that are difficult to quantify. Here we present the results of three different methods to date a sedimentary unit consisting of diatomaceous ooze and diatomaceous mud that was deposited following the last deglaciation at five core sites on the inner shelf in the western Amundsen Sea (West Antarctica). In three cores conventional 14 C dating of the AIO in bulk samples yielded age reversals down‐core, but at all sites the AIO 14 C ages obtained from diatomaceous ooze within the diatom‐rich unit yielded similar uncorrected 14 C ages between 13 517 ± 56 and 11 543 ± 47 years before present (a BP). Correction of these ages by subtracting the core‐top ages, which probably reflect present‐day deposition (as indicated by 210 Pb dating of the sediment surface at one core site), yielded ages between ca. 10 500 and 8400 cal. a BP. Correction of the AIO ages of the diatomaceous ooze by only subtracting the marine reservoir effect (MRE) of 1300 a indicated deposition of the diatom‐rich sediments between 14 100 and 11 900 cal. a BP. Most of these ages are consistent with age constraints between 13.0 and 8.0 ka for the diatom‐rich unit, which we obtained by correlating the relative palaeomagnetic intensity (RPI) records of three of the sediment cores with global and regional reference curves. As a third dating technique we applied conventional radiocarbon dating of the AIO included in acid‐cleaned diatom hard parts extracted from the diatomaceous ooze. This method yielded uncorrected 14 C ages of only 5111 ± 38 and 5106 ± 38 a BP, respectively. We reject these young ages, because they are likely to be overprinted by the adsorption of modern atmospheric carbon dioxide onto the surfaces of the diatom hard parts prior to sample graphitisation and combustion for 14 C dating. The deposition of the diatom‐rich unit in the western Amundsen Sea suggests deglaciation of the inner shelf before ca. 13 ka BP. The deposition of diatomaceous oozes elsewhere on the Antarctic shelf around the same time, however, seems to be coincidental rather than directly related. Copyright © 2009 John Wiley & Sons, Ltd.

Safety Assessment of Lactobacillus plantarum 423 and Enterococcus mundtii ST4SA Determined in Trials with Wistar Rats - K. Ramiah; K. ten Doeschate; Rob Smith; Leon M. T. Dicks (Probiotics and Antimicrobial Proteins, 2009)

Differential induction of apoptosis and inhibition of the PI3-kinase pathway by saturated, monounsaturated and polyunsaturated fatty acids in a colon cancer cell model - Anna-Mart Engelbrecht; Joe-Lin du Toit-Kohn; Beverly Ellis; Mark Thomas; Theo Nell; Rob Smith (Apoptosis, 2008)

Indirect effects of algae on coral: algae‐mediated, microbe‐induced coral mortality - Jennifer E. Smith; Morrigan Shaw; Rob A. Edwards; David Obura; Olga Pantos; Enric Sala; Stuart A. Sandin; Steven Smriga; Mark Hatay; Forest L. Rohwer (Ecology Letters, 2006)
Declines in coral cover are generally associated with increases in the abundance of fleshy algae. In many cases, it remains unclear whether algae are responsible, directly or indirectly, for coral death or whether they simply settle on dead coral surfaces. Here, we show that algae can indirectly cause coral mortality by enhancing microbial activity via the release of dissolved compounds. When coral and algae were placed in chambers together but separated by a 0.02 μ m filter, corals suffered 100% mortality. With the addition of the broad‐spectrum antibiotic ampicillin, mortality was completely prevented. Physiological measurements showed complementary patterns of increasing coral stress with proximity to algae. Our results suggest that as human impacts increase and algae become more abundant on reefs a positive feedback loop may be created whereby compounds released by algae enhance microbial activity on live coral surfaces causing mortality of corals and further algal growth.

Year-round treatment of dairy wastewater by constructed wetlands in Atlantic Canada - Erin Smith; Rob Gordon; Ali Madani; Glenn Stratton (Wetlands, 2006)

Water quality impact of a dairy cow herd crossing a stream - Rob J. Davies‐Colley; John W. Nagels; Rob A. Smith; Roger G. Young; Chris J. Phillips (New Zealand Journal of Marine and Freshwater Research, 2004)
The water quality impact of a herd of 246 dairy cows crossing a stream ford was documented. Two cow crossings produced plumes of turbid water associated with very high concentrations of faecal indicator bacteria ( Escherichia coli ) and high suspended solids (SS) and total nitrogen (TN). On the first crossing, towards the milking shed, the cows were tightly‐bunched and produced a sharp spike of contamination ( E. coli peaking at 50 000 cfu/100 ml). After milking, the cows wandered back across the stream as individuals or small groups, and contaminants were less elevated, albeit for a longer period. Light attenuation, measured continuously by beam transmissometer, correlated closely with E. coli , SS, and TN, permitting the total yield of these contaminants to be estimated. Contaminant yields for the two crossings were very similar, suggesting that time taken and whether or not cows are herded may not greatly influence water quality impact. The cows defecated c. 50 times more per metre of stream crossing than elsewhere on the raceway. This study has shown that cattle accessing stream channels can cause appreciable direct water contamination, suggesting that excluding cattle from streams will have major water quality benefits.

Molecular cytogenetic analysis of a novel high-grade canine T-lymphoblastic lymphoma demonstrating co-expression of CD3 and CD79a cell markers - Rachael Thomas; Ken C. Smith; Rob Gould; Sue M. Gower; Matthew M. Binns; Matthew Breen (Chromosome Research, 2001)

Bacterial abundance and production in different water masses around South Island, New Zealand - Rob Smith; Julie Hall (New Zealand Journal of Marine and Freshwater Research, 1997)
Bacterial numbers and production were measured in the upper water column in the winter and spring of 1993 in five water masses surrounding the South Island of New Zealand. Average bacterial numbers and production were found to be higher in spring (8.5 × 10 5 cells ml −1 and 0.20 mg m 3 h −1 , respectively) than winter (5.5 × 10 5 cells ml −1 and 0.05 mg C m 3 h −1 respectively). Bacterial production was strongly correlated with chlorophyll a and primary production (P 0.001) in spring but not in winter. Spring bacterial production and at 10 m depth averaged across 28 stations was 23% of primary production, and with a growth efficency of 40%, may have consumed up to 57% of primary production. Bacterial biomass was greater than phytoplankton biomass for 75% of the 10 m depth comparisons during winter sampling and 44% during the spring sampling. The bacterial biomass was found to represent 24.6–33.5% of the nitrogen in particulate organic matter (

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Report of The Site Selection Committee to the PAA Business Meeting Wednesday July 27, 1994 - Brian L. Rex; Joe Sieczka; Alexander Pavlista; Duane Preston; Pete Weingartner; Robert O’Keefe; Jonathon Whitworth; Chesley E. Smith; Rob Davidson; Gregory Porter; Dan Hane; Terry Work (American Journal of Potato Research, 1994)